2013
DOI: 10.1093/eurpub/ckt131
|View full text |Cite
|
Sign up to set email alerts
|

Delays in diagnosis and treatment of breast cancer: a multinational analysis

Abstract: The delay in diagnosis and treatment of breast cancer remains a serious problem. Several psychological and behavioural patient attributes strongly determine both patient-related delay time and system-related delay time, but their strength is different in particular countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
119
4
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 15 publications
(17 reference statements)
10
119
4
6
Order By: Relevance
“…The majority of deaths from all types of cancer (70%) occurred in low and middle income countries (World Health Organization, 2014a). Furthermore, cancer survival tended to be poorer in developing countries, most likely because of a delayed diagnosis, low availability of the test or screening programs, limited access to standard treatment, fear of being diagnosed with cancer and not seeing oneself at risk (Rastad et al, 2012;Jassem et al, 2013;Norwati, …”
Section: Introductionmentioning
confidence: 99%
“…The majority of deaths from all types of cancer (70%) occurred in low and middle income countries (World Health Organization, 2014a). Furthermore, cancer survival tended to be poorer in developing countries, most likely because of a delayed diagnosis, low availability of the test or screening programs, limited access to standard treatment, fear of being diagnosed with cancer and not seeing oneself at risk (Rastad et al, 2012;Jassem et al, 2013;Norwati, …”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference between the variables such as age, place of residence, education, tumor stage, first noticed symptom of the women with 'system was late' evaluation in this group (Table 3). In the study by Jassem et al, system-related delays were shorter for women with at least intermediate levels of education and women aged more than 60 years (30). There was a significant relationship found between younger women who noticed a mass by themselves and system-related delays.…”
Section: Discussionmentioning
confidence: 89%
“…In their multinational study, Jassem et al (30) reported that the delay was shorter in women with an intermediate education level, in women who work, Min: minimum; max: maximum; SD: standard deviation *39 women were not included in this group because they were divorced, widowed or single.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados coinciden con los reportados en el estudio multinacional de Jassem, et al, en el cual la demora en el diagnóstico y el tratamiento se atribuyó en mayor medida al sistema de salud, con un tiempo promedio de 78 días (8). En el contexto latinoamericano, en otros trabajos como el de Trufelli, et al, llevado a cabo en un hospital público brasilero, se encontró que la mediana del tiempo que trascurría entre la sospecha de tumor detectado por mamografía y la biopsia, era de 72 días (17), lo que se aproxima a lo hallado en cuanto al T 2 en este estudio.…”
Section: Discussionunclassified